MODEL PENGEMBANGAN PERMAINAN BOLKET DALAM PEMBELAJARAN BOLA BESAR PENJASORKES SISWA KELAS V SD NEGERI KALONGAN 01 KECAMATAN UNGARAN TIMUR (Department of Physical Education, Sport, Health and Recreation, 2014)
Basketball is one of the big ball game learning in school, but in reality the learning process is not implemented optimally. Hence the need for modification in the learning process. The method used is according to research development Brog and Gall, as for product development procedures include: (1) a preliminary investigation and collection of information, including field observations and literature review. (2) Develop initial product form. (3) Evaluation of the experts. (4) Revision of the first product. (5) Test field. (6) Revision of the final product. (7) The final result is a model of learning through play basketball bolket for Elementary School fifth grade students Kalongan 01. data was collected using field observations and questionnaires were obtained from expert evaluation and the results of the questionnaire by the students. The data analysis technique used is descriptive percentages. Expert test results obtained average percentage of 84% product categories. Data results of questionnaires and observations of students in small groups of trials the average response obtained with the percentage of 75.69% either category. And questionnaire data from a large group of students test answers obtained with the percentage of 74.19% either category. Based on research data, it was concluded that the game bolket effective and in accordance with the characteristics of the students so that they can be used in Physical Education, Sport, Health and Recreations.